Efficiency of Co-Expression of Transcription Factors Pdx1, Ngn3, NeuroD and Pax6 with Insulin: A Statistical Approach - Toit, Don F. du; Longo-Mbenza, Benjamin; Page, Benedict J.; Tchokonte-Nana, Venant (International Journal of Statistics in Medical Research, 2013)
Aim: The objective of this study was to investigate the time related proﬁle and efﬁciency of co-expression of the homeodomain proteins Pdx1, NeuroD, Ngn3, Pax6 and caspase3 with insulin, and to establish the time periods post PDL optimum for islets transplantation. Study Design/Methods: In this experimental study, immunoﬂuorescent staining procedure was performed on deparafﬁnized pancreatic duct ligated (PDL) tissues of 78 Sprague–Dawley rats. Quantiﬁcation of protein coexpression was made using a computerized morphometry. The efﬁciency of co-expression was arbitrary deﬁned by the value of mean ratio (score without unit) of insulin expression divided by each expression index of the other proteins, occurring within the time interval of 12–24 h post PDL. Statistical tool was used to analyze the efﬁciency of co-expression of proteins; analysis of variances (one way ANOVA) was used to compare the means of co-expression indexes across the time periods pre- and post PDL. P-values less than 0.05 were considered statistically signiﬁcant; no post hoc test was done. Results: The curve of insulin expression showed a crossover with that of the co-expression at different time periods pre- and post PDL. The optimal or higher efﬁciency of co-expression was observed for insulin and Ngn3 co-expression, while a good or medium efﬁciency was noted for the co-expression of insulin with Pdx1, insulin with NeuroD and insulin with Pax6. Low or weak efﬁciency was observed for the co-expression of insulin with caspase3. Conclusion: We therefore propose an early islets transplantation using 12–24 h post PDL harvested pancreatic tissues. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>